Hikâyet-i temîm-i dârî (vr. 1-22) (inceleme- metin- dizin- tıpkıbasım) - Bulut, Elif Çelik (My University, 2015)
Hîkâyet-i Temîm-i Dârî isimli eser, Eski Anadolu Türkçesi dil özellikleri taşıyan manzum bir halk hikâyesidir. olarak eserin 1b-22b arasındaki kısmı çalışılmıştır. Eserin bilinen yirmi dört nüshasından biri olan bu yazma, Yapı Kredi Bankası Sermet Çifter Araştırma Kütüphanesi Yazmalar Kataloğu’nda 125 numarada “ Hikâyet-i Temîm-i Dârî ” adıyla kayıtlıdır. Bu nüsha, Dâvûd Ümmî tarafından yazılmış, 1868 tarihinde Süleyman Besim tarafından istinsah edilmiş olup harekeli, nesih hatlı, son varak boş olmak kaydıyla 46 varak, 13 satırdan oluşmaktadır. Avrupa kağıda yazılmıştır. Çalışmaya konu olan yazma, “b” yüzünden başlamaktadır. 5b ve 6b’de birer adet der-kenâr beyit bulunmaktadır. Bu der-kenâr beyitler hikâyenin akışına uygun ve konu ile alâkalı olduğundan diğer beyitler gibi numaralandırılmıştır. bu sayfaların dışında tüm sayfalar 13 satırdan oluşmaktadır. Hîkâyet-i Temîm Dârî tez çalışması dört ana bölümden oluşmaktadır: İnceleme- Metin- Dizin- Tıpkıbasım. Eserin birinci bölümü; eserin adı, konusu ve içeriği, hikâyenin özeti, müellif- müstensih, eser üzerinde yapılan çalışmalar, eserin sahası ve dili, eserin tavsifi, eserin gramer özellikleri, ses özellikleri, çekim ekleri, birleşik fiiller, kısaltmalar ve işaretler, çeviriyazı alfabesi, bibliyografya bölümlerinden oluşmaktadır. İkinci bölüm olan Metin bölümünde; eserin okunuşunda izlenen yol ile eserin transkripsiyonlu metni yer almaktadır. Üçüncü bölüm olan Dizin bölümünde ise bu bölümünün hazırlanmasında izlenen yol ve eserin söz varlığını ortaya koyan gramatikal dizini yer almaktadır. Dördüncü bölüm; Tıpkıbasımdır. Bu bölümde eserin Yapı Kredi Bankası Sermet Çifter Araştırma Kütüphanesi Yazmalar Kataloğu’nda 125 numarada kayıtlı “Hîkâyet-i Temîm Dârî ”nin çalışılan kısmı olan 1b-22b arası Arap harfli olarak yer almaktadır. Eserde hikâyeye adını veren Temîm Dârî adlı bir sahabenin cinler tarafından kaçırılıp yedi yıl zarfında yaşadıkları konu edilmektedir. Eserin dili sade ve akıcıdır. Eserde Temîm’in başına gelen hadiseler bir sonraki olayı ya da sonucu merak ettirecek nitelikte anlatılmıştır.

This study which is titled Hîkâyet-i Temîm-i Dârî, depicts a folk tale in verse which was written in Arabic and carrying the features of the Old Anatolian Turkish language. The part of the work that we have studied as the master's degree is the part between 1b and 22b. This copy which is one of the copies of the known twenty four copies of the work is registered as “Hikâyet-i Temîm-i Dârî” in the number 125 at the Yapı Kredi Bank's Sermet Çifter Research Library's Inscriptions Catalogue. This copy in naskh script with vowel marks, written by Dâvûd Ümmî and copied by Süleyman Besim in 1868, consists of 46 leaves whose last leaf is blank and 13 lines. İt was written on European Paper. The copy that is the subject of the study begins from the b side of the book. There is one postscript couplet on each 5b and 6b. As these postscript couplets are relevant and in accordance with the flow of the story, they are numbered as the other couplets. Outside these pages, all pages are composed of 13 lines. The work of art describes the seven years of one of the Companions called Temim Dari, who was abducted by jinns and gave his name to the story. The language of the work is simple and smooth. Events that happened to Temîm are narrated in a way that makes the audience wonder the next event or the end of the story. As every story written in the Islamic period, the work begins with the besmele, then the reason for that is explained and after that, the importance of praising and saying salavat to the Prophet Muhammed is expressed. The scribe starts the story by introducing Temîm Dârî and at the same time touching on the incomprehensible things of the world and mortality. The work ends with a prayer to the Prophet Muhammed and to his community. The work called Hîkâyet-i Temîm Dârî consists of four main parts: Analysis, Text, Index and Fascimile. The first part of the work covers the name, subjects, content and summary of the story, the studies on the author, scribe, translator and the work, its region and language, definition, spelling features, sound features, inflections, compound verbs, abbreviations ve symbols, transcription alphabet and bibliography. In the Text part which is the second part, the way to follow in reading the story and the transcribed text are found. In the third part which is called Index, the way followed in preparing the Index part and the grammatical index displaying the vocabulary of the work are expressed. The fourth part is called Fascimile. In this part, the studied part of the work, between 1b and 22b, which is registered as “Hikâyet-i Temîm-i Dârî” in the number 125 at the Yapı Kredi Bank's Sermet Çifter Research Library's Inscriptions Catalogue, is found in Arabic letters
Keywords: Türk dili